Childhood Emotional Neglect and Cognitive Function Among Middle-Aged and Older Adults: Mediating Role of Social Engagement - Wang, Weiwei (Journal of interpersonal violence, 2024)
Studies have demonstrated that childhood maltreatment and adverse experiences lead to impaired cognitive function. However, relatively few studies have examined the independent effect of childhood emotional neglect on cognitive function in middle-aged and older adults, and the role of social engagement in this relationship. Using a sample from the China Health and Retirement Longitudinal Study, the current study examined the mediating role of social engagement in the association between childhood emotional neglect and cognitive function among middle-aged and older adults. Participants were 32,540 middle-aged and older adults (Mage = 63.45, SD = 8.83). Data were analyzed using a fixed effects model for panel data and bootstrap resampling method. Results showed that participants who experienced emotional neglect had poorer cognitive function (β = −.068, p < .001). Social engagement mediated 7.55% of the association between emotional neglect and cognitive function (β = −.004, 95% CI [−0.006, −0.002], p < .05). The results indicated that interventions are required to improve awareness of emotional neglect and facilitate healthy parenting practices. Further research on how to motivate adults who experienced emotional neglect to engage in social activities is necessary.